Pengaruh Tingkat Kualitas Pelayanan dan Ketersediaan Fasilitas Jasa Samsat Keliling Terhadap Kepuasan Wajib Pajak di Kelurahan Sridadi Kecamatan Muara Bulian Kabupaten Batang Hari - AZ, Siti Marina; Ratna, Ratna; Maisarah, Siti; Delima, Rts. Hartha (Universitas Batanghari Jambi, 2024)
This research aims to determine the effect of the level of service quality and the availability of mobile Samsat service facilities on taxpayer satisfaction in Sridadi Village. The research method used is quantitative descriptive using multiple linear regression analysis tools. The results of the research reveal that simultaneously and partially the service and facility quality variables have an influence on taxpayer satisfaction in Sridadi Village with an influence contribution of 49.8%.